HOUT-19. THE SHORT-TERM OVERALL SURVIVAL ASSOCIATED WITH SINGLE- VS. MULTI-AGENT CHEMOTHERAPEUTIC REGIMENS FOR 1p/19q-CODELETED WHO GRADE III ANAPLASTIC OLIGODENDROGLIOMAS: A NATIONAL EVALUATION. (11th November 2019) - Touat, Mehdi; Harary, Maya; Kavouridis, Vasileios; Smith, Timothy; Iorgulescu, Bryan
Abstract: INTRODUCTION: Although diffuse gliomas of oligodendrocytic lineage demonstrate chemosensitivity, the survival outcomes associated with single- (i.e. temozolomide; TMZ) or multi-agent (i.e. PCV) chemotherapy regimens remain uncertain for anaplastic oligodendrogliomas (AO). METHODS: Patients presenting between 2010–2016 with 1p/19q-codeleted WHO grade III AO were identified by ICD-O3 and site-specific factors from the National Cancer Database, which comprises >70% of cancers newly-diagnosed in the U.S. Predictors of receiving first-line single- vs. multi-agent chemotherapy were assessed by multivariable logistic regression. Overall survival (OS) was estimated by Kaplan-Meyer approaches and evaluated by multivariable Cox regression. RESULTS: There were 952 patients with 1p/19q-codeleted WHO grade III AO and complete first-line chemotherapy data, with: 13.9% (n=132) no-, 75.0% (n=714) single-, and 11.1% (n=106) multi-agent chemotherapy. In logistic regression of chemotherapy-treated AOs, more recent diagnosis was associated with higher multi-agent (OR=1.48/year, 95%CI=1.25–1.74, p< 0.001) rates; otherwise there were no associations of single- vs. multi-agent chemotherapy with patient sex, age-at-diagnosis, race, insurance status (reference=privately insured), comorbidity index, tumor greatest dimension, tumor location (reference=frontal lobe) or crossing of midline, nor with radiotherapy or EOR (all p >0.05). Multi-agent usage rose from 3.6% in 2010 to 24.3% in 2016. Median follow-up was 34.9mos (IQR=18.8–54.8). The unadjusted 5yr-OS rate was 57.4% (95%CI=43.5–69.1) for no chemotherapy, 72.1% (95%CI=67.1–76.5) for single-agent, and 77.5% (95%CI=59.9–88.1) for multi-agent. Cox regression (adjusting for the above variables of radiotherapy and EOR, patient demographics, and tumor characteristics) demonstrated no significant OS difference between single- and multi-agent (HR=0.91, 95%CI=0.38–2.15, p=0.82) chemotherapy. CONCLUSIONS: In a national database of AOs managed in the 'real-world' setting, there is increasing utilization of multi-agent (i.e. PCV) chemotherapy; but no significant difference in risk-adjusted short-term mortality (i.e. ~3-5yrs after diagnosis) between first-line multi- and single-agent (i.e. TMZ) chemotherapy. These findings provide preliminary data while we await the long-term PFS and OS results from the CODEL trial.